2018
DOI: 10.1183/13993003.01290-2018
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the need for carbon dioxide monitoring in the investigation of paediatric sleep disordered breathing

Abstract: Overnight cardio-respiratory polygraphy without CO2 monitoring is adequate in children investigated for uncomplicated obstructive sleep apnoea

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…In Trucco et al's study, none of the 73 otherwise healthy children with mild OSA had AH 25% but nocturnal CO 2 results in those without OSA was not reported. 2 However, consistent with our results, these authors found no change in the management of otherwise healthy children with OSA when taking into account their nighttime CO 2 results. An important issue is the clinical relevance of the definition of AH because AH 25% is much higher than AH 2% .…”
supporting
confidence: 91%
See 2 more Smart Citations
“…In Trucco et al's study, none of the 73 otherwise healthy children with mild OSA had AH 25% but nocturnal CO 2 results in those without OSA was not reported. 2 However, consistent with our results, these authors found no change in the management of otherwise healthy children with OSA when taking into account their nighttime CO 2 results. An important issue is the clinical relevance of the definition of AH because AH 25% is much higher than AH 2% .…”
supporting
confidence: 91%
“…Interestingly, Trucco et al primarily found an impact of AH 25% on the management of children with neuromuscular diseases, but they did not test other AH definition. 2 The limitations of this study are its retrospective, single-center nature and sample size, and we acknowledge that confirmatory prospective studies are needed. For technical reasons, reliable TcPCO 2 was not always available throughout the children's sleep time, according to the trained pediatric sleep specialists working in our center of expertise, but we discarded TcPCO 2 recordings that were too short or representing less than 50% of TST.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…There are conflicting opinions regarding the utility of TcCO 2 in the diagnosis of pediatric SDB. Although it is recommended that CO 2 monitoring be considered in all patients undergoing PSG, 21 it has been argued that the measurement only has utility in children with comorbidities 22 . None of the children in the current study had comorbidities and our measures of TcCO 2 correlated poorly with standard PSG indices such as the MOAHI 1,2 .…”
Section: Discussionmentioning
confidence: 57%
“…Although it is recommended that CO 2 monitoring be considered in all patients undergoing PSG, 21 it has been argued that the measurement only has utility in children with comorbidities. 22 None of the children in the current study had comorbidities and our measures of TcCO 2 correlated poorly with standard PSG indices such as the MOAHI. 1,2 However, our measures of partial airway obstruction showed consistent correlations with the degree of change in TcCO 2 .…”
Section: Discussionmentioning
confidence: 62%